Encapsulating Peritoneal Sclerosis Secondary to Peritoneal Dialysis (Bangladesh Journal of Medicine, 2025)
Encapsulating peritoneal sclerosis (EPS) is a rare and morbid complication of peritoneal dialysis, characterized by peritoneal thickening, fibrosis, and encasement of the bowel. Here, we report a 37-year-old man who presented with encapsulating peritoneal sclerosis complicated by a significantly large, loculated fluid collection several months after discontinuation of peritoneal dialysis. The case, overall, highlights a lesser-known complication of peritoneal dialysis and provides clinical pearls for clinicians to optimize patient care.Bangladesh J Medicine 2025; 36(2): 139-141